Consent in Current Data Protection Act in Spain: New Legal Case Scenarios and New Requirements - del Castillo Vázquez, Isabel-Cecilia (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2020)
We hereby study the meaning of article 7 of General Data Protection Regulation (RGPD, in Spain) and article 6 of the Organic Act on the Protection of Data and Guarantee of Digital Rights (LOPDyGDD, in Spain), regarding the profiles entitled to the specifically legally binding consent to deal with personal data.
Keywords: Consent; Data Protection; Victim; Personal Data; EU Law; Spanish Law; Domestic Acts; Transposition